Characteristics of Direct-Coupling Fuel Cell Injection in Renewable Energy Hybrid Power Generation Electrical Systems: Karakteristik Injeksi Fuel Cell Secara Direct-Coupling Pada Sistem Kelistrikan Pembangkit Hibrida Energi Terbarukan - Sulistiyowati, Indah; Jamaaludin; Anshory, Izza (Procedia of Social Sciences and Humanities, 2022)
Currently, Fuel Cell technology is widely used as a supporting technology for energy storage systems in the electrical system. With the widespread use of renewable energy as an energy source today, several schemes have been tried for the installation of Fuel Cells after the converter, but the performance of the Fuel Cells is not very helpful because the response time is not significant enough to raise power requirements when input intermittent occurs (on a time scale of seconds). . In this study, a simulation of the installation of a fuel cell was carried out in an isolated electrical system (off-grid) containing solar panels. To increase the performance of the Fuel Cell, the installation will be carried out by Direct-Coupling before the converter. The results of this study indicate that the installation of Direct-Coupling can help improve the performance of Fuel Cells in off-grid renewable energy electrical systems.